2015
DOI: 10.1084/jem.20141836
|View full text |Cite
|
Sign up to set email alerts
|

CCL2-induced chemokine cascade promotes breast cancer metastasis by enhancing retention of metastasis-associated macrophages

Abstract: Kitamura et al. find a role for metastasis-associated macrophage (MAM) chemokine pathways CCL2–CCR2 and CCL3–CCR1 in promoting breast cancer cell pulmonary metastasis. Genetic deletion of CCR1 or CCL3 in a mouse model of breast cancer cell metastasis prevents MAM retention in the lung, reduces MAM-cancer cell interactions and reduces the number of lung metastatic foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
391
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 536 publications
(416 citation statements)
references
References 58 publications
12
391
0
Order By: Relevance
“…This is consistent with other studies showing that intravenously injected B16 melanoma cells develop more lung metastatic foci in Ccl3 -/ -mice than WT mice [10]. However, recent studies demonstrated that IMo are retained in the metastatic site through a CCL3-dependent mechanism [11] and promote tumor cell survival. It would be interesting to assess using conditional genetics whether PMo-derived CCL3 recruits NK cells and at the same time affects MAM retention.…”
supporting
confidence: 93%
“…This is consistent with other studies showing that intravenously injected B16 melanoma cells develop more lung metastatic foci in Ccl3 -/ -mice than WT mice [10]. However, recent studies demonstrated that IMo are retained in the metastatic site through a CCL3-dependent mechanism [11] and promote tumor cell survival. It would be interesting to assess using conditional genetics whether PMo-derived CCL3 recruits NK cells and at the same time affects MAM retention.…”
supporting
confidence: 93%
“…30,31 CCL-2 and CCL-3 in lung metastasis have not been fully discussed. However, a recent study which was conducted by Kitamura et al 32 demonstrated that CCL-2 had a therapeutic impact in breast cancer metastasis through enhancing several macrophages retention. Meanwhile, abundant evidence have referred the pivotal carcinogenesis of IL-8 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple studies have illustrated that CCL2/CCR2 axis signaling-mediated crosstalk between TAMs and tumor cells plays a critical role in macrophage recruitment in hepatocellular carcinoma and prostate cancer. [31][32][33] In light of this, we conducted western blotting and RT-qPCR assay to analyze the levels of key cytokines CCL2 secreted into medium. As expected, PKM2-shRNA treatment or siRNA-PKM2 transfection into HT-29 and Caco-2 cells caused a significant reduction in expression of mRNA and protein levels in CCL2 (Figure 3(a) and (b)).…”
Section: Pkm2 Contributes To Macrophage Recruitment By Regulation Ofmentioning
confidence: 99%